Double Tropopauses and the Tropical Belt Connected to ENSO. Issue 14 (14th July 2020) - Wilhelmsen, Hallgeir; Ladstädter, Florian; Schmidt, Torsten; Steiner, Andrea K.
Abstract: A detailed analysis of double tropopause (DT) occurrences requires vertically well resolved, accurate, and globally distributed information on the troposphere‐stratosphere transition zone. Here, we use radio occultation observations from 2001 to 2018 with such properties. We establish a connection between El Niño‐Southern Oscillation (ENSO) phases and the distribution of DTs by analyzing the global and seasonal DT characteristics. The seasonal distribution of DTs reveals several hotspot locations, such as near the subtropical jet stream and over high mountain ranges, where DTs occur particularly often. In this study, we detect a higher number of DTs during the cold La Niña state while warmer El Niño events result in lower DT rates, affecting the structure of the tropopause region. Close to the Niño 3 region, this relates to a much lower first lapse rate tropopause altitude during La Niña and corresponds to an apparent narrowing of the tropical belt there. Plain Language Summary: Double tropopauses (DTs) are associated with several phenomena in the transition zone between the troposphere and the stratosphere. DTs may occur when midlatitudinal and tropical air masses meet and warmer air overlaps colder air. A detailed analysis of DT occurrences requires accurate and globally distributed temperature information with high vertical resolution. In this study, we use radio occultation temperature observations from 2001 to 2018 with such properties. This enables us to establish a connection between the El Niño‐Southern Oscillation (ENSO) phases and the distribution of DTs and to analyze the global and seasonal DT characteristics. The seasonal distribution of DTs reveals locations where DTs occur particularly often. During the colder La Niña state of the ENSO, a higher number of DTs is detected, while the warmer El Niño events result in lower DT rates. Close to the tropics in the Pacific Ocean, this relates to a much lower tropopause height during La Niña, which corresponds to an apparent narrowing of the tropical belt. Key Points: Double tropopause characteristics and the connection to ENSO are analyzed using vertically high resolved GPS RO observations More double tropopauses are detected during the cold La Niña phase and less during El Niño During La Niña, a much lower first lapse rate tropopause corresponds to a narrowing of the tropical belt around the Niño 3 region